TECHNOLOGICAL ADVANCEMENTS AND THEIR INFLUENCE ON CONSUMER DECISION-MAKING IN HEARING AID ACQUISITION - Kumari, Pallavi; Niyogi, Anjan (International Journal of Research -GRANTHAALAYAH, 2024)
This paper reviews the impact of technological advancements on consumer decision-making regarding hearing aid acquisition, focusing specifically on the Indian context. While innovations like smartphone connectivity, AI-driven features, and rechargeable batteries increase purchase intention (Manchaiah et al., 2021), a complex interplay of cultural, socioeconomic, and accessibility factors influences adoption rates. The paper examines how the urban-rural divide (Kumar et al., 2020), affordability challenges (Reddy & Nair, 2019), and cultural nuances (Sharma & Patel, 2022) shape technology acceptance in India. It also explores the potential of Tele-audiology (Chopra & Sharma, 2021) and government initiatives (Kumar et al., 2021) in promoting wider access to advanced hearing aids. The review highlights the need for manufacturers to adopt segmented approaches, healthcare providers to expand telecom-services, and policymakers to implement inclusive policies to address the unique needs of the Indian market.